2018
DOI: 10.26417/ejis.v10i1.p7-17
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary View into Optimism and Pessimism in Emic Perspective

Abstract: The tradition of research of optimism and pessimism is very popular nowadays, but the past decades had offered a string of very interesting access into this phenomenon as within separate cultures so on the plan of crosscultural comparisons. The aim of this research was to establish to which extent the different variables describing the style and lifestyle of students in Bosnia and Herzegovina are connected with the level of optimism / pessimism. In that regard, beside the general information on examinees, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Descriptions of these lifestyles provide a broad framework of understanding current trends among youth, especially within the student population. In comparison to other surveys conducted in neighbouring countries, the results of our research show dramatic changes in terms of preferenced lifestyles 1 .…”
Section: Analysis Of Lifestyle Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…Descriptions of these lifestyles provide a broad framework of understanding current trends among youth, especially within the student population. In comparison to other surveys conducted in neighbouring countries, the results of our research show dramatic changes in terms of preferenced lifestyles 1 .…”
Section: Analysis Of Lifestyle Resultsmentioning
confidence: 76%
“…shows the obtained distribution of results. 1 For comparison purposes, in their research on a sample of 237 examinees, high school students in Bitola, Mladenovska-Dimitrovska and Dimitrovska (2015), they used the same scale and got a completely different ranking of life styles: among the high school students in Bitola, the most preferred lifestyle was family -sentimental style, then utilitarian, followed by egoistic and hedonistic orientation. Minimum preferred lifestyles in this research were: orientation to popularity, orientation to power and a cognitive lifestyle.…”
Section: Analysis Of Lifestyle Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The research conducted by Veenhoven (2007;after Rijavec et al, 2008, p.83) has shown that happiness is not merely individual private matter but it depends on numerous social factors, since the happiness of westerners is connected with a sequence of factors depicting the level of social justice achieved, such as: political and economic freedom, obeying the law, human rights, women' rights, low level of corruption and personal freedom. In our researches in the area of Bosnia and Herzegovina (Alić, Cerić and Habibović, 2013, 2015, 2017a, 2017b,2017c it was shown as in regard to evaluation of personal life satisfaction a level of empathy, the way of building up of social relations, sensitivity and social distance toward the others (in inter-group and outer-group relations), a family functionality, parental style / dominant behaviour examinees are exposed to, and preference of life styles have significant impact.…”
Section: Introduction and Theory Backgroundmentioning
confidence: 99%
“…Comparative examinations of happiness started in 60s of previous century and they are able to be found in World Database of Happiness 1 . According to last comparative data, among the happiest nations are Danish, Columbians.…”
Section: Introduction and Theory Backgroundmentioning
confidence: 99%